Pengaruh Spiritual Emotional Freedom Technique (Seft) Terhadap Penurunan Dismenore Primer Pada Remaja Putri - Erlin Puspita (Quality : Jurnal Kesehatan, 2018)
Primary dysmenorrhea is a certain type of pain that experienced by teenage girls during menstruation. Primary dysmenorrhea is caused by the imbalance of psychological and progesterone hormone in the blood and prostaglandins. Dysmenorrhea is common in most women. From the data obtained, dysmenorrhea interferes 50% of reproductive women and 60-85% in teenagers that resulting in a large number of absence in school. SEFT (Spiritual Emotional Freedom Technique) is one of the non-pharmacological techniques to reduce primary dysmenorrhea in teenage girls The purpose of this study was to determine the effect of SEFT on reduction of primary dysmenorrhea in teenage girls. The study was conducted from June to November 2017, using quasi experiments in one group (one group pre test-post test design) at SMPIT Putradarma. Sampling was taken by total sampling 97 people. The research analysis used dependent t test (Wilcoxon Signed Rank Test). The result showed that the average age of teenagers who experienced primary dysmenorrhea was 12 years 26 months. The results showed the decreasing in the intensity of primary dysmenorrhea pain before and after SEFT intervention and there was an effect of intervention SEFT in the decreasing of primary dysmenorrhea pain. Thus SEFT technique can be considered as one of the non-pharmacologic therapies in the reduction of pain.